Effect of oral protease inhibitor administration of gallbladder motility in patients with mild chronic pancreatitis - Sugiyama, Masanori; Atomi, Yutaka; Wada, Nobuaki; Kuroda, Akira; Muto, Tetsuichiro (Journal of gastroenterology, 1997)
Oral administration of a protease inhibitor (camostat) induces pancreatic hypersecretion via hormonal and neural systems in humans. Camostat may also affect gallbladder motility via these systems. The aim of this study was to evaluate the effect of camostat on gallbladder function. Gallbladder emptying in response to caerulein administration and to egg yolk ingestion was examined ultrasonographically in 15 patients with mild chronic pancreatitis before and after 6 months of camostat treatment, and in 10 control subjects. The plasma cholecystokinin concentration after yolk ingestion was measured by radioimmunoassay. Fasting gallbladder volume and contractile function, whether stimulated by caerulein or yolk, did not differ between pancreatitis patients before camostat treatment and controls. Plasma cholecystokinin levels, basal and yolk-stimulated, did not differ between nontreated pancreatitis patients and control subjects. Fasting volume had decreased significantly by 1, 3, and 6 months of camostat treatment, while contractile function was not affected. Camostat did not influence plasma cholecystokinin levels. Oral administration of a protease inhibitor appears to decrease fasting gallbladder volume via a mechanism other than cholecystokinin release.